Analysis of Sharia Literacy Level and Sharia Financial Inclusion PNM Mekaar Sharia in Increasing Income Public (Study on the Fishing Community of Kuala Jaya Hamlet, South Lampung Regency) - Ana Musta’anah; Kulup Bina Buono; Ria Atika; Heni Noviarita (Journal of Islamic Business and Economic Review, 2021)
The community requires financial literacy to manage finances in order to accomplish optimal goals and to make decisions about how to use financial institutions. A descriptive qualitative approach is used in this study, using a sample of 7 informants interviewed. Data is gathered through interviews, observations, and documentation. The credibility technique is used in the data validity technique.Internal validity (internal validity), exterior validity (external validity), dependability (reliability), and trustworthiness (objectivity). According to the findings of this study, the degree of Islamic education in the United States is at an all-time high. The fishing community in Dusun Kuala Jaya still has a poor level of financial literacy. In the meantime, the level of Islamic financial inclusion in the fishing community in the United States has increased. Dusun Kuala Jaya is a fantastic restaurant. Account ownership and saving are indicators of this. and traditional financial entities' financing